IMPLEMENTING THE PROJECT-BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES AT SMPN 01 SUKOWONO - Fila Fitliatul Rahmah; Fury Styo Siskawati; Tri Novita Irawati (Jurnal Penalaran dan Riset Matematika, 2026)
This study was conducted to examine student learning outcomes as indicators of learning achievement through preliminary interviews conducted at SMPN 01 Sukowono, Jember Regency. The findings revealed that teachers still predominantly applied teacher-centered instructional approaches, resulting in low student engagement, boredom, and limited understanding of the learning material, which consequently affected students’ mathematics achievement, particularly on the topic of three-dimensional geometric shapes with flat surfaces during the 2023/2024 academic year. This study aimed to determine the improvement in the learning outcomes of 25 students in Class VIII D through the implementation of the Project-Based Learning (PjBL) model. The research employed Classroom Action Research (CAR) using observation, tests, and documentation as data collection techniques. Data analysis focused on students’ achievement of the Minimum Mastery Criteria (KKM). The results demonstrated a significant improvement in student learning outcomes. In Cycle I, the classical mastery level reached 72%, with 18 students achieving mastery learning. In Cycle II, the mastery level increased to 100%, with all 25 students meeting the KKM standard. Therefore, the implementation of the PjBL model was proven effective in improving students’ mathematics learning outcomes by encouraging active participation, collaborative learning, and deeper conceptual understanding.